A perspective on the applications of energy-cyber-physical systems (e-CPSs) in ultra-low emission coal-fired power plants - Zhao, Haitao; Zheng, Chenghang; Džapo, Hrvoje; Liu, Shaojun; Guo, Yishan; Gao, Xiang; Wu, Tao (Elsevier, 2019)
To address the issue of air pollution in coal-fired power plants in China, the ultra-low emission (ULE) technology was proposed to control SO2, NOx and particulates, and ULE air pollution control devices have been quickly applied across the country. Although the ULE devices could work effectively for simultaneous removal of multi-pollutant, there is a great potential to efficiently control the emissions and to reduce the energy consumption by application of the energy-cyber-physical systems (e-CPSs). In order to explore the possibilities, the general conceptual overview of cyber-physical systems was first introduced, and then the feasible application in ultra-low emission coal-fired power plants were elaborated, along with an overview of major building blocks of such CPSs, including hardware components, devices for ultra-low emission air pollution control, industrial cloud, industrial software, and accompanying security systems. The perspective and benefits of application of e-CPSs in ultra-low emission coal-fired power plants were discussed, as a new modern approach for achieving more effective, efficient and reliable ULE air pollution control devices and the processes.